Examining the Forced Migration of Turkestanians: Reasons and Stories - YESEVİ, ÇAĞLA GÜL (Routledge Journals, Taylor & Francis Ltd., 2025)
Turkestanians migrated from West Turkestan - Soviet Central Asia - to Afghanistan, especially in the late 1920s and early 1930s. This article focuses on the definition of this migration and the reasons for the migration from Turkestan to Afghanistan. It examines the causes of this migration presented as religious and cultural reasons on the one hand and social and economic reasons on the other. The interviews with migrants and their families have shown that they had mainly migrated to preserve their religion and culture. This article is based on the findings from a research project conducted between 2018 and 2020, which included short questionnaires, in-depth interviews and ethnographic research held mainly in Istanbul, Turkey. Seventy-one in-depth interviews were conducted with Turkestanians living mostly in Turkey, Saudi Arabia, the USA and Kazakhstan. Recent studies on Turkestanian migration have emphasized the era's political history and political trends, and the views and activities of the Turkestanian elites and leaders towards the liberation of Turkestan. Nevertheless, the central claim of this article is to reveal the views of ordinary migrant people and their families through oral history. It examines the claims about how this migration is remembered and viewed by the Turkestanian diaspora. Therefore, the unrecorded and hidden stories could come to light, and the reasons for this migration could be better understood. This article will contribute to the scholarly investigation of Turkestanian migration in the late 1920s and early 1930s and the region's historiography.
Keywords: Turkestanian Migrants; Forced Migration; Reasons Formigration; Migration Stories